2017
DOI: 10.1007/8904_2017_61
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphenylalaninaemias in Estonia: Genotype–Phenotype Correlation and Comparative Overview of the Patient Cohort Before and After Nation-Wide Neonatal Screening

Abstract: The present study provides a retrospective overview of the cohort of phenylketonuria (PKU) patients in Estonia. Based on the available data, the patients clearly cluster into two distinct groups: the patients with late diagnosis and start of therapy (N = 46), who were born before 1993 when the national newborn screening programme was launched, and the screened babies (N = 48) getting their diagnoses at least in a couple of weeks after birth.Altogether 153 independent phenylalanine hydroxylase (PAH) alleles fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Despite this decrease, the p.Arg408Trp variant is still a leading cause of PKU with 49% (50 of 102 unrelated patient) of our PKU patients being homozygous for this mutation. These new data now establish Latvia as having the lowest frequency of the p.Arg408Trp variant of all the Baltic countries (Estonia 80% [ 12 ] and Lithuania 73% [ 8 ]). A recently published study from Russia reported the frequency of this variant to be 50.9%.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite this decrease, the p.Arg408Trp variant is still a leading cause of PKU with 49% (50 of 102 unrelated patient) of our PKU patients being homozygous for this mutation. These new data now establish Latvia as having the lowest frequency of the p.Arg408Trp variant of all the Baltic countries (Estonia 80% [ 12 ] and Lithuania 73% [ 8 ]). A recently published study from Russia reported the frequency of this variant to be 50.9%.…”
Section: Discussionmentioning
confidence: 86%
“…Unidentified PKU causing variants in the PAH gene is also reported in other populations e.g. in Estonia in 2 of 94 patients were not identified none of pathogenic variants and in 2 of 94 patients were not identified second pathogenic variant [ 12 ]. It is proposed that PCR amplification and sequencing of all exons and adjacent introns achieves pathogenic variant detection in case of PKU - > 95–99%, and large deletion/ duplication analysis <0.05% of variants [ 2 ].…”
Section: Discussionmentioning
confidence: 92%
“…Here we have not isolated the cases where female patients have become pregnant and therefore had stricter regulations of the diet. One reason for the difficulty of maintaining the Phe levels in blood in the observed patients may be the severity of particular PAH mutation, as the p.Arg408Trp variation vastly predominant in Estonian population [ 9 ] completely abolishes PAH activity, if present in homozygous state.…”
Section: Discussionmentioning
confidence: 99%
“…The initial created database included 4290 entries from 69 patients. All patients were carefully classified by genotype/phenotype data and these results have been previously published [ 9 ]. All data from individuals with initially suspicious samples obtained by newborn screening, but not confirmed with HPA, were excluded, as well as Phe levels confirming the newborn screening results and data obtained from a Phe loading/cofactor tetrahydrobiopterin (BH 4 ) test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation